Assessment of the Scope of Work for Operational Control of Steel Underground Gas Pipelines, Taking Into Account the Organizational and Logistical Factor - N. V. Strutsky; V. N. Romaniuk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
One of the main types of maintenance of steel underground gas distribution pipelines is periodic instrument inspection. This inspection is a kind of operational control, which includes detection of defects of insulation coating and gas leaks by instrumental methods, without opening the pipeline. This simultaneously controls two different levels of failure of the gas pipeline’s serviceability, one of which fully preserves its operability, but creates the possibility of a chain of events threatening to cause a failure in the future (insulation defect), while the other level of failure is, in fact, the case when the failure has already occurred (loss of tightness of the gas pipeline), but before the examination was not detected. All underground gas distribution pipelines are subjected to an instrument inspection with a certain regulatory frequency. The identified damages are subject to mandatory elimination, the serviceability and operability of the gas pipeline are being restored. Thus, periodic instrument inspection is a key technical measure that ensures the management of the technical condition of steel underground gas distribution pipelines. It should be mentioned that the work carried out during the inspection and further repair of gas pipelines is the most extensive and labor-consuming of all those performed on the linear part of the gas distribution system. Accordingly, adequate planning in this area is very important from the point of view of both the reliability and safety of the gas distribution network and the economic and economic one. At the same time, it is quite difficult to ensure the required adequacy of operational control planning and maintenance of engineering facilities in practice, since the maintenance process itself combines regulated and unregulated components and has significant inertia of management. The present article is devoted to the issues of reasonable forecasting of the scope of work on the instrument inspection of steel underground gas pipelines, taking into account a specially identified complex organizational and logistical factor reflecting the influence of existing production practices and management approaches in the field of gas distribution. The forecast is based on the currently relevant time series analysis methods.